A chemically induced proximity system engineered from the plant auxin signaling pathway. Issue 26 (21st June 2018) - Zhao, Weiye; Nguyen, Huong; Zeng, Guihua; Gao, Dan; Yan, Hao; Liang, Fu-Sen
Abstract : A new chemically induced proximity system is developed by engineering the plant auxin signaling pathway. Abstract : Methods based on chemically induced proximity (CIP) serve as powerful tools to control cellular processes in a temporally specific manner. To expand the repertoire of CIP systems available for studies of cellular processes, we engineered the plant auxin signaling pathway to create a new indole-3-acetic acid (IAA) based CIP method. Auxin-induced protein degradation that occurs in the natural pathway was eliminated in the system. The new IAA based method is both readily inducible and reversible, and used to control the production of therapeutic proteins that induced the apoptosis of cancer cells. The approach is also orthogonal to existing CIP systems and used to construct a biological Boolean logic gate controlling gene expression system. We believe that the new CIP method will be applicable to the artificial control and dissection of complex cellular functions.